2015
DOI: 10.1111/pce.12531
|View full text |Cite
|
Sign up to set email alerts
|

Rice cyclophilin OsCYP18‐2 is translocated to the nucleus by an interaction with SKIP and enhances drought tolerance in rice andArabidopsis

Abstract: Cyclophilin 18-2 (CYP18-2) genes, homologues of human peptidyl-prolyl isomerase-like 1 (PPiL1), are conserved across multicellular organisms and Schizosaccharomyces pombe. Although PPiL1 is known to interact with ski-interacting protein (SKIP), a transcriptional co-regulator and spliceosomal component, there have been no functional analyses of PPiL1 homologues in plants. Rice cyclophilin 18-2 (OsCYP18-2) bound directly to amino acids 56-95 of OsSKIP and its binding was independent of cyclosporin A, a cyclophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…One example is BnCYP18-1 which is the only B. napus homolog of AtCYP18-2 with a full length CLD (with 95% sequence identity, Table 2). It has been shown that the Arabidopsis CYP AtCYP18-2 is recruited by AtSKIP to the nucleus to regulate pre-mRNA splicing 55 . Because of the high homology, the oilseed rape variant might fulfil a similar role in the nucleus of B. napus cells.…”
Section: Resultsmentioning
confidence: 99%
“…One example is BnCYP18-1 which is the only B. napus homolog of AtCYP18-2 with a full length CLD (with 95% sequence identity, Table 2). It has been shown that the Arabidopsis CYP AtCYP18-2 is recruited by AtSKIP to the nucleus to regulate pre-mRNA splicing 55 . Because of the high homology, the oilseed rape variant might fulfil a similar role in the nucleus of B. napus cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cytochromes (CYPs) are immunophilins, and several CYP family members had been discovered in model plants such as A. thaliana , Oryza sativa , P. trichocarpa , Morus notabilis , and Carica papaya [3741]. In rice, OsCYP20-2 was shown to take part in the abiotic stress response, and overexpression of OsCYP18-2 by interacting with ski-interacting protein (SKIP) can enhance drought tolerance in rice and Arabidopsis [42]. Additionally, SKIP was also found to participate in splicing precursor mRNA in Arabidopsis [43], and the cis - and trans -isomerase peptidyl-prolyl isomerase-like 1 is recruited by SKIP into the spliceosome where precursor mRNA splicing occurs [44], suggesting that overexpression of OsCYP18-2 affected the expression of alternative splicing variants of stress-related genes by SKIP under drought condition [42].…”
Section: Discussionmentioning
confidence: 99%
“…In rice, OsCYP20-2 was shown to take part in the abiotic stress response, and overexpression of OsCYP18-2 by interacting with ski-interacting protein (SKIP) can enhance drought tolerance in rice and Arabidopsis [42]. Additionally, SKIP was also found to participate in splicing precursor mRNA in Arabidopsis [43], and the cis - and trans -isomerase peptidyl-prolyl isomerase-like 1 is recruited by SKIP into the spliceosome where precursor mRNA splicing occurs [44], suggesting that overexpression of OsCYP18-2 affected the expression of alternative splicing variants of stress-related genes by SKIP under drought condition [42]. Cyclophilin is suggested to be an unspecific stress-responsive protein in plants and plays a role in the defense response, and it was upregulated in potato and tobacco under stresses [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…A company (Abfrontier, Seoul, Korea) carried out peptide synthesis, immunization, and antiserum purification. Immunoblot analysis was performed as described previously (Lee et al, 2015b). The prepared polyclonal CYP21-4 antibody was hybridized with total potato and rice proteins from the leaf tissue, and the CYP21-4 protein bands were confirmed as having the predicted size (determined from the mobility of recombinant OsCYP21-4 protein).…”
Section: Methodsmentioning
confidence: 99%
“…The representative model plants, Arabidopsis and rice have established classification systems for the immunophilin family of receptors (He et al, 2004; Ahn et al, 2010). Previously, we classified rice immunophilins, including 29 OsFKBPs and 26 OsCYPs (Ahn et al, 2010), and used reverse genetics to identify stress-responsive rice CYPs involved in salt, drought, photosynthetic, and cold stress (Park et al, 2013; Seok et al, 2014; Lee et al, 2015a,b, 2016; Yoon et al, 2016). In addition, rice CYP21-4 (OsCYP21-4) was identified as an unusual Golgi-localized immunophilin that contributes to oxidative stress tolerance by regulating peroxidase activity (Lee et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%